Malagueira for all: A research project for public empowement and heritage protection - Guilherme, Pedro (2022)
Malagueira, Património de Todos, Subsídios para a sua classificação: Pedro Guilherme (University of Évora) Included on the recent national indicative list of UNESCO World Heritage sites, the housing development of Malaguiera, designed by the Portuguese architect Álvaro Siza Vieira, is distinct because it successfully addresses difficult land use issues many large scale projects are forced to grapple with: the growing urbanization of rural areas, the construction of a new neighbourhood in coexistence with an old city, and the then new phenomena of popular participation during Portugal’s revolutionary period (1970s). Malagueira’s recent tentative listing spurred a project led by the University of Evora to identify, recognise and systematise the values associated with tangible and intangible cultural heritage and to promote MALAGUEIRA.PT as a new brand that integrates cultural, architectural, historical, social and scientific values.